Iron man 3 [videorecording (DVD)] - Black, Shane; Downey, Robert, Jr., 1965-; Paltrow, Gwyneth, 1972-; Cheadle, Don; Pearce, Guy, 1967-; Hall, Rebecca, 1982-; Dale, James Badge, 1978-; Sadler, William, 1950-; Ferrer, Miguel, 1954-2017; Favreau, Jon; Kingsley, Ben, 1943- (Paramount : distributed by Buena Vista Home Entertainment, 2013)
When Tony Stark/Iron Man finds his entire world reduced to rubble, he must use all his ingenuity to survive, destroy his enemy, and somehow protect those he loves. But a soul-searching question haunts him: Does the man make the suit, or does the suit make the man?